2006
DOI: 10.1111/j.1601-183x.2006.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

ApoE allelic variability influences pupil response to cholinergic challenge and cognitive impairment

Abstract: Exaggerated pupil response to dilute tropicamide has been suggested as an early biological marker for Alzheimer’s disease. The current study links apolipoprotein E (ApoE) allelic variability to the magnitude of pupil response in a sample of community‐dwelling elderly without a diagnosis of Alzheimer’s disease or dementia. Possession of an ɛ4 allele influences both the likelihood of exhibiting an exaggerated pupil response above a predetermined cut‐off (13% above baseline diameter) and the absolute overall magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Subsequent experiments by Iijima et al ( 68 ) found that significant differences in pupil sizes were found at a lower dose of tropicamide (0.005%), potentiating the possibility for a diagnostic screening test. Scinto ( 69 ) further investigated pupil involvement in AD and located a clear biological link between ApoE allele status and pupillary response to dilute tropicamide. Nevertheless, the use of the tropicamide test as a diagnostic tool for AD is controversial, as other studies have failed to find significant results ( 70 72 ).…”
Section: Pupilmentioning
confidence: 99%
“…Subsequent experiments by Iijima et al ( 68 ) found that significant differences in pupil sizes were found at a lower dose of tropicamide (0.005%), potentiating the possibility for a diagnostic screening test. Scinto ( 69 ) further investigated pupil involvement in AD and located a clear biological link between ApoE allele status and pupillary response to dilute tropicamide. Nevertheless, the use of the tropicamide test as a diagnostic tool for AD is controversial, as other studies have failed to find significant results ( 70 72 ).…”
Section: Pupilmentioning
confidence: 99%
“…Recently, Scinto showed that Apolipoprotein E (ApoE) allelic variability, a factor linked to late-onset, sporadic AD [52,53], influences pupil response to cholinergic challenge via tau hyperphosphorylation [54]. Furthermore, Scinto reported in a prospective longitudinal study that there is an increased risk with a hypersensitive pupil response for developing significant cognitive impairment in areas of memory attention and language in a pattern that is consistent with pre-clinical AD, and the risk is even higher with ApoE allelic variability [55].…”
Section: Pupil Size Changes In Admentioning
confidence: 99%
“…The STS is associated with a variety of brain regions linked with the processing of social information ( 77 82 ). It has been found that parts of the STS respond to specific visual and auditory stimuli Including facial expression and gaze ( 83 93 ), bodies ( 16 , 17 , 80 , 88 ), point-light walkers ( 15 , 68 , 79 , 89 , 90 ), human voices ( 20 , 91 ), language ( 21 , 92 ), and the audiovisual integration of speech ( 22 , 93 ). Furthermore, the temporoparietal junction (TPJ) which lies posterior and superior to the STS controls theory of mind tasks ( 94 ), in which participants interpret the actions of characters in stories.…”
Section: Associations Between Cim and Hmmentioning
confidence: 99%